Comparative Proteomics of Rice Endosperm for the Discovery of Starch Biosynthetic-Related Enzymes - Nikson Fatt-Ming, Chong; Hasnain, Hussain (Universiti Malaysia Sarawak, 2022)
Starch biosynthesis is still not fully understood. The current models of starch biosynthesis focus on four key enzymes, with limited understanding of how these key enzymes and their multiple isoforms are coordinated to synthesise starch granules. Apart from the currently known key enzymes, there are potentially other proteins that may be involved in starch biosynthesis and have not yet been discovered. A comparative proteomics analysis of EM653, a sugary rice mutant, and Taichung 65, its wild type, has been carried out to identify differentially expressed proteins (DEPs) with possible involvement in starch biosynthesis. The EM653 mutant is deficient in isoamylase (Isa), one of the key enzymes in starch biosynthesis. It exhibits a sugary phenotype, where phytoglycogen is synthesised instead of amylopectin. The pleiotropic effect of the Isa deficiency in sugary rice affects the expression of associated starch biosynthetic enzymes. Two complementary comparative proteomics approaches were used in this study to identify DEPs in sugary and normal rice endosperm. A gel-free shotgun approach, liquid chromatography with tandem mass spectrometry (LC-MS/MS) was used to analyse proteins from the enriched amyloplastic fraction of sugary and normal rice endosperm. A total of 929 proteins were identified, of which 160 were differentially expressed. Meanwhile, a gel-based approach, two-dimensional gel electrophoresis coupled with LC-MS/MS (2DE-LC-MS/MS) was used to analyse endosperm proteins and 40 DEPs were identified. Next, the gene expression of seven target genes in sugary and normal rice was determined through quantitative polymerase chain reaction (qPCR) using a relative quantification approach. For three genes directly involved in starch biosynthesis (Isa1, PPDK1 and PPDK2), mRNA expression was correlated with the protein expression. Next, in silico analysis of the DEPs was carried out to identify proteins with possible involvement in starch biosynthesis. Notably, this study had identified two poorly characterised amylases, OsBam8b and plastidial Amy3, which may be directly involved in starch biosynthesis. A xylanase inhibitor protein (XIP) that may act as an amylase inhibitor with potential involvement in starch metabolism was also identified. This analysis also showed the importance of energy metabolism in starch biosynthesis with 15 DEPs found crucial in ensuring an adequate energy supply to sustain starch synthesis during endosperm development. Other than that, 11 DEPs were found to be involved in the partitioning of carbon flow between the various metabolic pathways which likely affects endosperm development. Lastly, eight DEPs were found to be involved in the endoplasmic reticulum (ER) protein processing which indirectly affects starch biosynthesis. This study has several potential applications. OsBam8b and plastidial Amy3 may have industrial applications such as in the baking, bio-alcohol, and animal feed industry. Meanwhile, based on its potential role as an amylase inhibitor, XIP has potential applications as a pesticide in agriculture and as a treatment for diabetes. In conclusion, this study has identified additional proteins with potential involvement in starch biosynthesis. Further studies to investigate the role of these proteins are needed as new findings will lead to new perspectives which may be vital for the elucidation of starch biosynthesis in plants. This will open up opportunities for crop improvement, which is essential for food security.